Revitalizing traditional wisdom: Exploring medicinal, plant-based healthcare practices in Kalatop-Khajjiar Wildlife Sanctuary, Himachal Pradesh, India - Sumit; Singh, Sumit; Kumar, Gulshan; Singh, Kanwaljeet (Ethnobotany Research and Applications, 2025)
Background: The Kalatop-Khajjiar Wildlife Sanctuary in the Western Himalayas is home to rich biodiversity and indigenous communities with deep-rooted ethnomedicinal traditions. These communities have relied on local flora for generations to treat common ailments using sustainable, plant-based healthcare practices. However, rapid socio-cultural changes and habitat pressures threaten the continuity of this traditional knowledge. Ethnobotanical documentation of such practices is crucial for conservation, cultural preservation, and potential pharmacological exploration. This study seeks to explore, record, and revitalize plant-based healing traditions within this ecologically and culturally significant landscape. Methods: Twelve field surveys were conducted in the 11 villages in and around Kalatop-Khajjiar Wildlife Sanctuary. A total of 140 informants (74 males and 66 females) between the ages of 21-80 years were interviewed using semi-structured questionnaires. The collected ethnomedicinal data was analyzed using the use-value (RFC) and informant consensus factor (ICF). Results: The present study reported 114 medicinal plants to treat 60 ailments. The results indicated herbs (75%) as the dominantly used growth form and leaves (40.1%) as the most frequently used plant parts. The herbal preparations were consumed mostly in paste form (33.3%) followed by decoction (27.1%), powder (12.2%), juice (6.9%), eaten raw (5.6%), poultice and infusion (4.9% each), cooked (2.1%), rubbed and oil (1.4%) and smoke (0.7%). Acorus calamus L. and Viola canescens Wall, were among the most highly cited plant species. Informant Consensus Factor (ICF = 0.90) was highest for parasitic conditions, followed by urological problems (ICF= 0.87), respiratory diseases (ICF= 0.86), digestive disorders (ICF= 0.85) and eye diseases (ICF= 0.85). New uses were reported for several plant species such as Adiantum venustum D.Don (Hair fall, Piles), Arisaema jacquemontii Blume (Knee Pain), Artemisia indica L. (Jaundice, Headache), Berberis lycium Royle (Kidney stones, Sore throat), Neolitsea pallens (D.Don) Momiy. & H.Hara. (Body ache). Conclusions: This study provides valuable information regarding the traditional knowledge associated with the medicinal use of plant species. While the medicinal efficacy of several widely utilized plant species such as Acorus calamus, Artemisia absinthium, Berberis lycium, Podophyllum hexandrum, Valeriana jatamansi, Malaxis muscifera, Urtica dioica, and Viola canescens have already been scientifically validated. However, species such as Anaphalis triplinervis, Arisaema jacquemontii, Cautleya spicata, Neolitsea pallens, Primula denticulata, Ranunculus distans, Reinwardtia indica, Rosularia rosulata, Solidago virgaurea, and Verbascum thapsus require comprehensive pharmacological and phytochemical investigations. Keywords: Kalatop Khajjiar Wildlife Sanctuary, Indigenous medicine, Ethnobotany, Chamba